Assessing brain iron and volume of subcortical nuclei in idiopathic rapid eye movement sleep behavior disorder. Issue 10 (20th May 2021) - Zhang, Xuan; Chai, Chao; Ghassaban, Kiarash; Ye, Jingyi; Huang, Yaqin; Zhang, Tong; Wu, Wei; Zhu, Jinxia; Zhang, Xianchang; Haacke, E Mark; Wang, Zhiyun; Xue, Rong; et al.
Abstract: Study Objectives: The relationship of iron with cognitive and motor impairment in idiopathic rapid eye movement sleep behavior disorder (iRBD) remains unknown. Methods: Twenty-nine (29) patients and 28 healthy controls (HCs) underwent susceptibility weighted imaging and susceptibility mapping. These images were used to evaluate the nigrosome-1 (N1) sign in the substantia nigra (SN), global and regional high-iron (RII) content, and volume of subcortical nuclei. Results: The number of iRBD patients with N1 loss (12) was significantly higher than HCs (2) ( p = 0.005). Compared with HCs, the iRBD patients had reduced volume of the right caudate nucleus (RCN) ( p < 0.05, false discovery rate [FDR] correction) but no significant changes in global and RII iron of the subcortical nuclei (all p > 0.05, FDR correction). Multiple regression analysis revealed that: for cognitive function, the RII iron of the RCN was significantly correlated with visuospatial function and the global iron of the right dentate nucleus (RDN) was correlated with memory function; for motor function, the RII iron of the left DN (LDN) and global iron of the left CN correlated with the Alternate-Tap test (left, average), the global iron of the LDN correlated with the Alternate-Tap test (right), and the global iron of the left GP correlated with the 3-m Timed Up and Go test (all p < 0.05, FDR correction). Conclusions: Our exploratory analysis found that iRBD patients had a higher incidence of N1 loss and reduced RCN volume after FDR correction. Cognitive and motor impairment were associated with iron deposition in several cerebral nuclei after FDR correction.